Plasmid Profile of Multiple Antibiotics Resistant (mar) Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus Isolated from Water Samples from Ebira Communities in Ekiti South Senatorial District - Odeyemi, Adebowale; Oluwole, Olusola; Adebayo, Adewole; Iseyemi, Seyifunmi (International Journal of Biological Research, 2016)
Plasmid curing of microbes and physicochemical analysis of water samples obtained from Ebira communities in six local governments in Ekiti SouthÂ Senatorial District were analyzed. Antibiotic sensitivity and profile of bacterial isolates were analyzed using pour plating, disk diffusion method and gelÂ electrophoresis techniques respectively while the plasmid were cured using acridine orange.Â The mean total bacterial count of the water samples collected from these six different local governments at different time ranged from 2.08 x 105 to 6.0 x 106 CFU/ml; the mean total coliform count ranged from 2.41 x 105 to 3.75 x 106 CFU/ml and the mean total Escherichia coli count (TEC) ranged from 1.53 x 105 to 3.45 x 105 CFU/ml. Total of 152 bacteria were recovered with E.coli having the highest distribution of 35% while Serratia marcensens had the least distribution of 0.7%. The highest antibiotic resistance of 100% was recorded against ceftazidine but only 17% of the isolates were resistant to gentamicin. About 56% of 34 selected MAR isolates carried plasmid(s) with high molecular weight ranging from 5.64Kbp to 23.13Kbp. Antibiotic resistance pattern and plasmids profile of selected MAR E.coli, Pseudomonas aeruginosa and Staphylococcus aureus prior to and after curing showed that Pseudomonas aeruginosa became susceptible to augmentin and Staphylococcus aureus also became susceptible to ceftriazole while E. coli still maintained the earlier resistant pattern. The plasmid profiling of these isolates after curing indicated the lost of plasmids in each of the isolates. Present study however implicated the incidence of MAR bacteria in the sources of water in Ekiti-South Senatorial district as a serious health challenge, and confirmed the potential of acridine orange for plasmid curing.